Ecosystem restoration centered in people - Mansourian, Stephanie; Djenontin, Ida N. S.; Elias, Marlene; Oldekop, Johan A; Derkyi, Mercy A. A.; Kull, Christian A.; Pacheco, Pablo (Wiley, 2025)
Ecosystem restoration is primarily led by biodiversity and climate change imperatives, often disregarding associated yet complex social, cultural, political, economic, institutional, and behavioral aspects. Ultimately, it is people who take decisions on, carry out, and are impacted by restoration. The sociopolitical contexts in which ecosystem restoration takes place, stakeholders' decisions leading to degradation or motivations to restore, influencing factors such as values, norms, and power relations, the restoration activities and their outcomes on people all constitute critical human dimensions. Yet, these dimensions are less understood and, therefore, rarely fully integrated into ecosystem restoration policy or practice. We introduce a five‐pillar framework to support ecosystem restoration strategies, projects, and programs to analyze, plan, revise, and improve their design and implementation by effectively integrating human dimensions. Without attending to these human considerations, we cannot achieve—in a just, equitable, and sustainable manner—ambitious restoration targets and address the interrelated crises of biodiversity loss, climate change, and land degradation.